Karakteristik Campuran SMA Kasar Menggunakan Batu Sungai Siwi Desa Minanga Kabupaten Mamasa - Sujanri Sugama Simak; Alpius; Charles Kamba (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
This research aims to utilize Siwi River stones in a mixture of the Rough Asphalt Stone Matrix (SMA). The methodology in this study is the Conventional Marshall and Marshall Immersion methods that produce characteristic values of Siwi River rocks, fillers, stability, flow, VIM, VMA, and SMS (Residual Marshall Stability), as well as optimum asphalt levels (KAO). After calculating the asphalt content, it is used asphalt levels of 6.00%, 6.25%, 6.50%, 6.75%, and 7.00%. The test results obtained a rough aggregate number: of 72%, fine aggregate: of 12.50%, filler: of 8.50%, and SMS: of 95.10% with the use of KAO of 7.00%.